Action libérale populaire and the legacy of Catholic Republicans in the French Third Republic - Myrick, Richard (Kansas State University, 2023)
At the dawn of the twentieth century, French Catholics attempted to build a political movement based on Catholic principles, rejecting the anti-republicanism that had marked the French Right since the Revolution of 1789. Inspired by the Ralliément, an admonition by Pope Leo XIII for faithful Catholics in France to work within the republican parliamentary system rather than to advocate for its elimination, the constitutional liberal Jacques Piou and the social Catholic Albert de Mun founded the Catholic Republican party Action libérale populaire on a platform of constitutional rights, social reform, anti-socialism, and fiscal conservatism. This dissertation studies the formation, growth, and challenges of Action libérale populaire during the period between its founding in 1901 and the advent of the First World War in 1914, with an emphasis on the party’s turning point in the legislative elections of 1906. Opposed by both Intransigents on the Right and Anti-clericals on the Left, Piou and de Mun attempted to unite Catholic Republicans, social Catholics, and secular Republicans within a sustainable Center-Right coalition. With a highly efficient organization, nationwide reach, and a consistent message, the party grew rapidly into the largest mass party in France. However, its inability to secure a legislative majority in the elections of 1906 and the subsequent disintegration of its coalition led to the party’s association with historical narratives of failure and decline. These narratives of failure and decline are assessed by analyzing the formation, growth, and tactics employed by Action libérale populaire’s leaders in building their coalition, as well as the challenges they encountered from both allies and opponents. This study approaches questions of success and failure from the divergent views and goals of the party’s two founders and challenges the narratives of failure and decline as incomplete. Instead, this dissertation argues that the Catholic Republican movement was largely successful in the longer term, failing only to produce a coalition that could advance the cause of constitutional reform. This more expansive view of Action libérale populaire and the Catholic Republican movement necessitates a reassessment of the French Right during the Third Republic and beyond.
Keywords: France; Third Republic; Politics